A Theoretical Model of Physical Function and Mobility Apprehension in Persons with Amputation of a Lower Limb. Issue 4 (October 2021) - Mathis, Shannon L.; Welch, Maggi R.
ABSTRACT: Introduction: An avoidance behavior is an inhibitive response to normal activities of daily life based on actions taken to escape movement in tasks that one considers challenging. In persons with lower-limb amputation, pain catastrophizing, the tendency to ruminate and magnify painful sensations, is a risk factor for mobility apprehension, an avoidance behavior. Avoidance behavior leads to physical deconditioning of the muscles. The purpose of this study was to link the psychological trait of avoidance to physiological traits of strength for the purpose of understanding balance. It was hypothesized that in persons with lower-limb amputation, poor balance will correlate directly with mobility apprehension and indirectly with muscular strength. Materials and Methods: Adult participants who had a well-fitting prosthesis and had the ability to ambulate at least 10 ft were asked to participate in the study. Participants completed questionnaires regarding demographic information and self-report instruments measuring mobility apprehension. Mobility apprehension was measured using the Tampa Scale for Kinesiophobia (TSK). Balance was measured using the Berg Balance Scale. A handheld dynamometer was used to assess isometric strength of the left and right hip extension, trunk flexors, and trunk extensors. Hip strength was defined as the mean value of the strength of the left and right hip extensors. Core strength was defined as the mean strength value between the trunk flexors and extensor muscles. Results: Of the participants, 80% reported comorbidities (e.g., diabetes, high blood pressure, and heart disease). The mean (SD) TSK score was 38.65 (6.68), where a score of 39 or higher indicates a high level of mobility apprehension. The mean (SD) hip and core strengths were 15.78 (9.29) lb and 5.60 (3.17) lb, respectively. The mean (SD) Berg Balance score was 46.25 (6.74). There was a moderate direct correlation between balance and hip strength ( r = 0.45, p = 0.046). Core strength approached a significant direct correlation with balance ( r = 0.39, p = 0.085). However, mobility apprehension was not related to balance. Conclusion: Results may assist clinicians in aiming exercise programs toward increasing hip and potentially core strength, thus improving balance to promote better mobility for individuals with a lower-limb amputation.